2020
DOI: 10.1007/jhep07(2020)098
|View full text |Cite
|
Sign up to set email alerts
|

D3-brane loop amplitudes from M5-brane tree amplitudes

Abstract: We study loop corrections to scattering amplitudes in the world-volume theory of a probe D3-brane, which is described by the supersymmetric Dirac-Born-Infeld theory. We show that the D3-brane loop superamplitudes can be obtained from the tree-level superamplitudes in the world-volume theory of a probe M5-brane (or D5-brane). The M5-brane theory describes self-interactions of an abelian tensor supermultiplet with (2, 0) supersymmetry, and the tree-level superamplitudes are given by a twistor formula. We apply t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 55 publications
4
29
0
Order By: Relevance
“…However, in contrast to the maximally supersymmetric case, the half-integrand I (1) NS does not vanish for tadpole-like worldsheet geometries, 34 and we thus expect the worldsheet formulas to lead to unphysical poles in the loop integrand. Contributions from similar poles in the 'linear' 32 We prove these statements in section 8.2. 33 This construction does indeed give the pure Yang-Mills integrand in the 'linear' formalism, i.e., with the 'old' one-loop scattering equations [24].…”
Section: Jhep10(2020)074mentioning
confidence: 69%
See 1 more Smart Citation
“…However, in contrast to the maximally supersymmetric case, the half-integrand I (1) NS does not vanish for tadpole-like worldsheet geometries, 34 and we thus expect the worldsheet formulas to lead to unphysical poles in the loop integrand. Contributions from similar poles in the 'linear' 32 We prove these statements in section 8.2. 33 This construction does indeed give the pure Yang-Mills integrand in the 'linear' formalism, i.e., with the 'old' one-loop scattering equations [24].…”
Section: Jhep10(2020)074mentioning
confidence: 69%
“…Both have been fruitful for studying theories of massless particles, most importantly gauge theory and gravity, and have brought numerous insights. They have also been extended to loop level, in various approaches; see, e.g., [11][12][13][14][15][16][17][18][19][20] for the BCFW recursion relations and [21][22][23][24][25][26][27][28][29][30][31][32][33] for the scattering equations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a beautiful CHY formula based on polarized scattering equations, appeared for the complete tree-level S-matrix of the N = 4 probe D3-brane (N f = 4 and N s = 6), as well as similar formulae for the 6d parent theories describing probe N = (1, 1) D5-and N = (2, 0) M5-branes [16]. Such higher-dimensional constructions have recently been used to obtain 1-loop integrands for the D3-brane theory in dimensional regularization [17].…”
Section: Review Of D3-brane Worldvolume Eftsmentioning
confidence: 86%
“…Then, at z = 1, the shifted momenta are projected onto the 3d subspace normal to N µ : p µ i N µ z=1 = 0. We implement this shift in terms of spinor-helicity brackets via the holomorphic shift 17) where N = N µ σ µ and a i are constants constrained by momentum conservation,…”
Section: D → 4d Oxidation: Subtracted Recursion Relationsmentioning
confidence: 99%
“…A study of one-loop corrections to specific brane models with additional fields can be found in[86][87][88].…”
mentioning
confidence: 99%